(untitled) (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
The purpose of this research is to describe how listening and pronunciation education techniques are through the use of songs and to find out whether the use of songs can help improve students pronunciation and listening skills in learning English. This research is a classroom action research. The population in this study were 2nd grade high school students. This type of research is a test, in the form of an oral test and a written test, observation sheets and documents. Thus, this study can suggest that the use of songs should be used robotically in every learning activity because in these activities students will be able to recognize what they are learning. It is recommended that the use of songs that are simple, fun, enjoyable, comfortable, and convenient to study can also help student learning